A New Anatomical and Surgical Landmark in Internal Abdominal Oblique Muscle: Fat Triangle - Madaen, Kazem; Niknafs, Behrooz (Urology Journal, 2012)
Purpose: To determine the anatomical landmark within the internal oblique muscle. Materials and Methods: In a prospective study, the abdominal wall was examined for internal oblique muscle land marks in 900 patients undergoing laparatomy. Results: There was a fat line at anterior superior iliac spine level to access the underlying layers and then to the abdominal cavity. Conclusion: A fat triangle within the internal oblique muscle provides a suitable region of surgical incision at the lower part of the abdominal wall.